The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/2179-8087.038416
|View full text |Cite
|
Sign up to set email alerts
|

Digital Approach for Measuring Tree Diameters in the Amazon Forest

Abstract: Buttresses and other natural structures modify the shape of stems in Amazonia and change the diameter at breast height (DBH) measured at 1.3 m at ground level. The lack of adequate measurement techniques affects negatively forest dynamics analyses and biomass estimating. The study evaluated an indirect method of measuring diameters in trees with DBH > 40 cm using principles of digital photogrammetry. The results obtained with two cameras (smartphone and Sony) were compared with direct measurements using diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Previous studies comparing repeated diameter measurements on the same trees have already reported measurement errors with the tape measure when the measuring tool is not oriented perpendicular to the vertical axis of the stem (Clark, 2002;Phillips et al, 2002;Elzinga et al, 2005;Grogan and Schulze, 2008;Butt et al, 2013). Visual estimates of diameter, for which diameter measurements on the irregularities of large trees are not accessible, even with the use of a scale, also lead to significant errors (Grogan and Schulze, 2008;Muller-Landau et al, 2014;Celes et al, 2019). In addition, these types of measurements are notoriously unreliable and lead to significant overestimates of the diametric growth of irregular trunk trees (Clark and Clark, 1996;Muller-Landau et al, 2014).…”
Section: Influence Of Tree Size On Diameter Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies comparing repeated diameter measurements on the same trees have already reported measurement errors with the tape measure when the measuring tool is not oriented perpendicular to the vertical axis of the stem (Clark, 2002;Phillips et al, 2002;Elzinga et al, 2005;Grogan and Schulze, 2008;Butt et al, 2013). Visual estimates of diameter, for which diameter measurements on the irregularities of large trees are not accessible, even with the use of a scale, also lead to significant errors (Grogan and Schulze, 2008;Muller-Landau et al, 2014;Celes et al, 2019). In addition, these types of measurements are notoriously unreliable and lead to significant overestimates of the diametric growth of irregular trunk trees (Clark and Clark, 1996;Muller-Landau et al, 2014).…”
Section: Influence Of Tree Size On Diameter Growthmentioning
confidence: 99%
“…The development of remote sensing technology such as Terrestrial Laser Scanning (TLS) and Close-Range Photogrammetry (CRP) has opened up new possibilities for obtaining diameter measurements at different heights along the trunk of tropical trees (Nölke et al, 2015;Bauwens et al, 2017Bauwens et al, , 2021Momo Takoudjou et al, 2018;Celes et al, 2019;Martin-Ducup et al, 2020;Akpo et al, 2020Akpo et al, , 2021Cushman et al, 2021;Witzmann et al, 2022). They have proven to be promising technologies for harmonizing the diameter measurement of irregular trunk trees at 1.30 m above the ground in the tropics (Nölke et al, 2015;Bauwens et al, 2017Bauwens et al, , 2021Cushman et al, 2021;Witzmann et al, 2022).…”
Section: Introductionmentioning
confidence: 99%